Research Gap Of E-Hrm: A Systematic Review - Harry Harry; Iryani Iryani (SEIKO : Journal of Management & Business, 2022)
The aim of this study to identify five research questions: (RQ1) the trend of E-HRM publications in the Google Scholar database in 2000-2023; (RQ2) publishers that published the most E-HRM articles; (RQ3) active researcher; (RQ4) most cited article titles; and (RQ5) publication network map. The research method uses a systematic review. The data is sourced from the Google Scholar database which is limited in terms of: (1) the type of bibliography used; and (2) keywords used "E-HRM". Research gap mapping using VOSviewer, and data analysis techniques use descriptive statistics. The results of the study indicated (1) 980 E-HRM-themed publications; (2) ResearchGate is a publisher that publishes the most E-HRM-themed articles; (3) the writer who actively researches E-HRM namely H.J.M. Ruël; and (5) there are 10 clusters that have the opportunity to become research gaps related to the E-HRM theme. The results of the study indicate that the E-HRM theme is still under-researched and has the potential to become a research gap in management, especially HRM. Keywords: Research Gap, E-HRM, Systematic Review.